2023
DOI: 10.1097/mcg.0000000000001828
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biologics for the Treatment of Inflammatory Conditions of the Pouch

Abstract: Background: Patients with medically-refractory ulcerative colitis or advanced neoplasia are often offered an ileal-pouch-anal anastomosis to restore bowel continuity. However, up to 50% of patients can suffer from inflammatory conditions of the pouch, some of which require biological therapy to treat. The aim of this study was to determine the efficacy of each biological agent for the treatment of inflammatory conditions of the pouch. Materials and Methods:A comprehensive literature search was performed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Other treatments are usually recommended for refractory patients or those with specific contraindications to anti-TNF-α drugs [ 108 ]. The real-life data for the use of UST in this setting are still scarce and limited by small sample sizes and large heterogeneity of therapy protocols/outcome definitions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 35 , 45 , 47 , 48 , 55 , 61 , 62 , 63 , 68 , 69 , 70 , 71 , 72 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other treatments are usually recommended for refractory patients or those with specific contraindications to anti-TNF-α drugs [ 108 ]. The real-life data for the use of UST in this setting are still scarce and limited by small sample sizes and large heterogeneity of therapy protocols/outcome definitions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 35 , 45 , 47 , 48 , 55 , 61 , 62 , 63 , 68 , 69 , 70 , 71 , 72 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , …”
Section: Resultsmentioning
confidence: 99%
“…The anti-TNF-α drugs were able to achieve in the short-and long-term (12 months) remission in about 50% of patients [107]. Other treatments are usually recommended for refractory patients or those with specific contraindications to anti-TNF-α drugs [108]. The real-life data for the use of UST in this setting are still scarce and limited by small sample sizes and large heterogeneity of therapy protocols/outcome definitions [9][10][11][12][13][14][15][16][17][18][19][20][21]35,45,47,48,55,[61][62][63][68][69][70][71][72][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: Ust For Pouchitismentioning
confidence: 99%
“…No association with CRP was established. The study conducted by Brewer et al34 employed a meta-analysis approach to evaluate the findings of 2 retrospective observational studies involving 26 cases of CARP and 1 retrospective observational study involving 52 cases of CARP-CD. The results indicated that the rate of complete response observed at an average of 7 months was 50% in CARP cases.…”
mentioning
confidence: 99%